Assessing the Effect of Saturation Variations on the Factor of Safety of Slopes in Elgon Sub-Region. - Muboki, Peterson (Kabale University, 2024)
In the challenging terrain of the Elgon sub-region, where slope stability is critical, this research project investigates the intricate relationship between saturation variation and the safety of slopes. This study combines field investigations and geotechnical analyses to unravel the impact of changing water content on slope behavior. I began by conducting a series of geotechnical tests. The Particle Size Distribution (PSD) analysis reveals intriguing trends; as you descend through the soil profile, gravel and sand content increase, while silty/clay content decreases. These variations have significant implications for slope stability. Silty/clay-rich soils dominate the region, but their fine-grained nature leads to reduced shear strength. When saturated, these soils become even more vulnerable, resulting in lower Factor of Safety (FOS) values for the slopes. The FOS, a critical parameter in slope stability assessments, exhibits a clear inverse relationship with saturation levels. As water content rises, the FOS decreases. This underscores the importance of considering saturation variations when evaluating slope stability. The findings also emerge from direct shear tests, which highlight potential weaknesses at specific depths likely attributable to the interplay between saturation and soil properties. In conclusion, this research contributes valuable insights into geotechnical engineering practices in the Elgon sub-region. By understanding how saturation affects slope stability, we can develop informed management strategies for similar geological settings. Ultimately, this study work serves as a stepping stone toward safer and more resilient slope designs in challenging landscapes.